The Phenomenon of Job Crafting in Hospitality Industry - Fiea Nursela Pusponegoro; Ade Irma Anggraeni; Dwita Darmawati (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
This study aims to determine the effect of Job Burnout in the relationship between job crafting, perceived organizational support and job performance. This research was conducted by involving 282 Hotel’s frontliners in Purwokerto Banyumas. SEM analisys was carried out to test the hypothesis. According to the data accomplished in the research, it was found out that: (1) The Respondents showed that they did Job Crafting during their works and it made the job performance's level increased. The relationship of the Job Crafting and Job performance was positively significant because the value of C.R is greater than the value of the t table, C.R> t table (2.333> 1.960). (2) Meanwhile, the Job Burnout in this study mediates the relationship between POS and job performance. This fact was proven by the value of the t value that was higher than the t table, it was 2.148 > 1,960 by using = 0,05. After all, it can be summed up that Job Burnout mediates the effect between POS and job performance.